Sustainable Cities of the Future: The Behavior Change Driver - Newman, Peter (American University, Washington College of Law, 2010)
Imagine a city that uses 100 percent renewable energy... where most transport is by electric light rail, biking, or walking . . . where the solar office block is filled with green businesses, where the local farmers’ market sells fresh, bioregional produce . . . where parents meet in the parks and gardens while their children play without fear in streets that are car-free. This is a reality in Vauban, a new eco-city of 5,000 households within Freiburg, Germany. 1 And in nearby Hanover, a city of 500,000 people has reduced its greenhouse gas emissions by fifty percent. 2 How did these communities transform their cultures to make the transition that every city now faces? Vauban and Hanover took the opportunity to use every policy lever possible at every step of the way—from planning to delivery—to ensure that the goal of sustainability drove each decision. These policy levers will be outlined and new data will be provided regarding the education lever, which involves behavior change and cultural adaptation